Evaluation of the Level of Sensitivity of Anopheles to Insecticides Used in Public Health in the Town of Kindu - Priss, Tambwe Mwabi; Bonny, Assani Wakenge; Alphonse, Masandi Milondo; John, Kahozi Mihali; Désiré, Kibonge Pascal; Jeanne d’Arc, Iragi Mundinga; Placide, Mbungi Pangalala (British Journal of Healthcare and Medical Research, 2024)
Vector control is one of the national malaria control strategies in the DRC, which is mainly based on the use of insecticides using the mass distribution of long-lasting insecticide-treated nets and intra-home spraying of insecticide. The general objective of this study is to evaluate the level of sensitivity of anopheles to insecticides used in public health. We carried out a descriptive study that consisted in describing the bio-ecological parameters of anopheles gites and determining their behaviour towards conventional insecticides. After carrying out quality control on the consistency of the data collected, they were entered into Excel 2010 and the analyses were carried out on the Statistical Package for the Social Sciences 23 (SPSS 23) software. The gambiae sl Anopheles tested showed different behaviours depending on the site and type of insecticides, and the Deltamethrin test showed a mortality rate of 99% in Basoko and 52% in RVA. After pre-exposure to the PBO, mortality was 98% at RVA. The permethrin test recorded a mortality rate of 79% at BASOKO and 31% at RVA. An increase in the sensitivity of Anopheles gambiae sl was observed after pre-exposure to 5% PBO. This resistance is largely of metabolic origin linked to mono oxygenase P450. In view of these results, it is imperative to consider new control strategies to control the emergence of this resistance.